PANDANGAN GENERASI MUDA TERHADAP CHILDFREE DAN PERAN MATA KULIAH PENDIDIKAN AGAMA ISLAM DALAM PENCEGAHAN CHILDFREE - Prasetya, Irwan; Hadikusuma, Riza; Febrian, Muhamad Reza; Setiawan, Angellia Malika Putri (Politeknik Negeri Jakarta, 2024)
The issue of Childfree has gone viral recently, especially after several cyber influencers such as YouTube, Twitter, Instagram revealed that their families had decided not to have children. Childfree itself is a decision made by a married couple not to have children. Indonesia as a country that believes in God makes religion a source of reference for behavior, one of which is in starting a family and having children. The role of religion is certainly very important in efforts to see the problems that occur and take the right solutions so that Childfree can be addressed wisely. This research aims to look at the views of the younger generation towards Childfree and the role of Islam in efforts to prevent the younger generation from being Childfree. Because the condition of the nation in the future will be determined by today's young generation. The research method chosen is a qualitative method using observation, interviews, documentation studies so that you will get in-depth results including the reasons for each research subject. The first pre-field stage, namely preparing a plan, selecting a field, preparing instruments. The second stage is data collection, and the third stage is data processing which consists of data display, analysis, drawing conclusions, and narrating the results. The results of this research showed that 82.35% of the research sample knew about Childfree from the internet, social media and other digital media. There was one sample who was affected by Childfree because they were worried about difficulties in taking care of children, especially due to busyness and economic factors, so they chose to postpone or not even have children. However, the majority of the sample still wants to have children after marriage. The role of religion is very important for all samples because they still remember advice from their teacher/lecture that said